Plasmatic osteopontin and vascular access dysfunction in hemodialysis patients: a cross-sectional, case–control study (The OSMOSIS Study) - Contenti, Julie; Durand, Matthieu; Vido, Sandor; Declemy, Serge; Raffort, Juliette; Carboni, Joseph; Bonnet, Sophie; Koelsch, Christophe; Hassen-Khodja, Réda; Gual, Philippe; Mazure, Nathalie M.; Sadaghianloo, Nirvana (Journal of nephrology, 2022)
Background and aims Despite close follow-up of patients with native arteriovenous fistulas (AVFs), up to 10% experience thrombosis each year. The OSMOSIS Study (Osteopontin as a Marker of Stenosis) tested the hypothesis that the systemic osteopontin level, a pro-inflammatory mediator related to vascular remodelling and intimal hyperplasia, increases in AVF stenosis, and may be used in clinical surveillance. Methods Our cross-sectional study compared the level of plasmatic osteopontin (pOPN) between patients with a well-functioning AVF (control group) and patients who required revision of their AVF due to stenosis (stenosis group). Blood samples were collected before dialysis (control group) or before intervention (stenosis group) from the AVF arm, and from the opposite arm as a within-subject control. pOPN level was measured by enzyme-linked immunosorbent assay. Results A total of 76 patients were included in the study. Baseline characteristics were similar between the groups (mean age, 70 years; men, 63%; AVF duration, 39 months), apart from prevalence of type 2 diabetes (T2D) (control group, 33%; stenosis group, 57%; p = 0.04). pOPN levels were similar between the AVF arm and the contralateral arm (551 ± 42 ng/mL vs. 521 ± 41 ng/mL, respectively, p = 0.11, paired t-test). Patients in the stenosis group displayed a higher pOPN level than patients in the control group (650.2 ± 59.8 ng/mL vs. 460.5 ± 61.2, respectively, p = 0.03; two-way ANOVA). T2D was not identified as an associated factor in a multivariate analysis ( p = 0.50). Conclusions The level of pOPN in hemodialysis patients was associated with the presence of AVF stenosis requiring intervention. Thus, its potential as a diagnostic biomarker should be assessed in a vascular access surveillance program. Graphic abstract